PENGARUH TRAIT KEPRIBADIAN BIG FIVE TERHADAP KEPERCAYAAN KONSUMEN UNTUK BERBELANJA PADA TOKO ONLINE - Intan Pandina; Gumgum Gumelar (Journal of Research and Measurement in Psychology, 2013)
Abstract This study aims to know the effect of big five personality traits against consumers trust for shopping in online shop. The research takes 120 subjects who ever did spending in online shop and domiciled in Jakarta. The methods was used in this research is quantitative approach with the regression analysis. The taking of sample in this study uses a nonprobability accidental sampling method. Instrument of this study consists of two scales, there are scale of consumers trust according to Mcknight, Kacmar, and Choudhury theory and scale of big five personality traits which had been adopted and modified from organization of International Personality Item Pool (IPIP) based on NEO-PI-R. The study result explains that there is significant effect between the big five personality traits against consumers trust for shopping in online shop. Regression equation obtained is Y = 38,315 + 0,044 X1 + 0,076 X2 + 0,406 X3 + 0,269 X4 + 0,067 X5, which means there is a positive effect between the big five personality traits against consumers trust for shopping in online shop with the value F = 4,618; p = 0,001 < 0.05 (significant). The amount of effect (Adjustment R Square) to the occurrence of the big five personality traits and consumers trust for shopping in online shop is 0,132 which means that the big five personality traits affect to consumers trust for shopping in online shop by 13,2% and the remaining 86,8% affected by another factors, outside of the big five personality traits. Keywords: Consumers Trust, Big Five Personality Traits, Online Shop.